Front Cover, Volume 1, Number 1, July 2022. Issue 1 (29th July 2022) - Zhang, Nan; Zhang, Huimin; Xu, Wanghuai; Gu, Haojie; Ye, Shimeng; Zheng, Huanxi; Song, Yuxin; Wang, Zuankai; Zhou, Xiaofeng
Abstract : Front Cover : The cover image is based on the Research Article A droplet‐based electricity generator with ultrahigh instantaneous output and short charging time by Zhang et al.